Raised intracranial pressure and cerebral blood flow: 2. Supratentorial and infratentorial mass lesions in primates - Johnston, I. H. (1973)
Changes in cerebral blood flow with increasing intracranial pressure were studied in anaesthetized baboons during expansion of a subdural balloon in one of two different sites. With an infratentorial balloon, cerebral blood flow bore no clear relation to intracranial pressure, but was linearly related to cerebral perfusion pressure. Apart from an initial change in some animals, cerebrovascular resistance remained constant with increasing intracranial pressure, and autoregulation appeared to be lost from the outset. With a supratentorial balloon, cerebral blood flow remained constant as intracranial pressure was increased to levels around 60 mm Hg, corresponding to a cerebral perfusion pressure range of approximately 100 to 40 mmHg. Cerebrovascular resistance fell progressively, and autoregulation appeared to be effective during this phase. At higher intracranial pressure levels (lower cerebral perfusion pressure levels), autoregulation was lost and cerebral blood flow became directly dependent on cerebral perfusion pressure. The importance of the cause of the increase in intracranial pressure on the response of the cerebral circulation and the relevance of these findings to the clinical situation are discussed.